2018
DOI: 10.1080/21691401.2018.1457535
|View full text |Cite
|
Sign up to set email alerts
|

Linalool loaded on glutathione-modified gold nanoparticles: a drug delivery system for a successful antimicrobial therapy

Abstract: In the present study, antimicrobial activity of Linalool loaded on Glutathione-modified Gold nanoparticles prepared by novel method was investigated. The aim of this study is to evaluate the antimicrobial activity of Linalool-gold nanoparticles (LIN-GNPs) against Gram's positive bacteria Staphylococcus aureus, Gram's negative bacteria Escherichia coli, and against Leishmania tropica. Gold nanoparticles were synthesized using the chemical method. Colour change, UV-Vis spectrum, FTIR and SEM confirmed the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Acridine orange was taken up via viable cells and emitted green fluorescence. Ethidium bromide was taken up only via nonviable cells and emitted red fluorescence through intercalation with harm DNA [15]. Cells line was seeded with density (1×10 4 ) on the cover slide that was located at the 12-well plate with ZnO nanoparticles.…”
Section: Acridine Orange/ethidium Bromide (Ao/eb) Dual Stainingmentioning
confidence: 99%
“…Acridine orange was taken up via viable cells and emitted green fluorescence. Ethidium bromide was taken up only via nonviable cells and emitted red fluorescence through intercalation with harm DNA [15]. Cells line was seeded with density (1×10 4 ) on the cover slide that was located at the 12-well plate with ZnO nanoparticles.…”
Section: Acridine Orange/ethidium Bromide (Ao/eb) Dual Stainingmentioning
confidence: 99%
“…The findings have confirmed that the small size of nanoparticles is supporting the ease of entering microbial cell membrane and thereby allowing inhibition mechanisms to activate within the cell [26]. It may also be explained by the involvement of reactive oxygen species (ROS) production [27,28], and accumulation of nanoparticles within the cytoplasm or outer membranes [29,30], disruption of the cell membrane and oxidative stress [31]. Findings illustrate that Gram-positive bacteria (Strept.…”
Section: Antimicrobial Activitymentioning
confidence: 69%
“…This method related optical density (OD) of the culture media at 220 nm to the time. As shown in against bacterial strains such as Staphylococcus and Escherichia coli [24]. Another study showed the ability of carbon NPs decorated with cupric oxide in reduction of bacterial growth [25].…”
Section: Antibacterial Activity Of Fe 3 O 4 -Pegmentioning
confidence: 94%